Inclusive and Women-friendly in a time of Diversity? The Scandinavian citizenship regime – the ‘childcare lesson’ - Cecilie Thun (Nordic Journal of Social Research)
In this article, I ask: Is the Scandinavian citizenship regime inclusive and women-friendly in a time of diversity? I approach this question by addressing the intersection of gender and ethnicity in relation to social citizenship with the main concern being childcare. I emphasize Norway as a case but also see Norway in comparison with Sweden and Denmark. In comparative studies, the Scandinavian citizenship regime is presented as being the most ‘women-friendly’. However, faced with an increasingly multicultural population, a pertinent question is whether this citizenship model is able to accommodate diversity. I explore two tensions that are basic to the inclusiveness and women-friendliness of the Scandinavian citizenship regime in diverse societies: 1) The tension between principles of gender equality and cultural diversity, and 2) the tension between liberating and controlling aspects of the welfare state. This article discusses the Norwegian family policy ‘hybrid’, which combines dual-earner support with traditional breadwinner elements. One might say that the Norwegian family ‘hybrid’ can be a solution to the tension between, on the one hand, a specific gender-equality family norm, and, on the other hand, the respect for other family norms. However, I argue that there is a double standard with regard to minority women, and it can be understood in light of a discourse about Norwegianness. Parental choice is considered a good thing – as long as the mother in question is considered ‘fully’ Norwegian. However, assumed cultural and ethnic differences – often based on stereotypical collective categories of difference – are used as boundary-markers between the majority and minorities. I conclude that, despite variations, all the Scandinavian countries grapple with the same tensions, and that there is a Scandinavian double standard regarding minority women.